Independent predictors of forecasting the course of congenital HIV infection in children - V. B. Denisenko; E. M. Simovanyan (LLC "Diagnostics and Vaccines", 2021)
The purpose is to characterize the clinical and laboratory parameters in children with different rates of congenital HIV infection progression and, based on the data obtained, to develop independent predictors of forecasting the course of the disease.Research methods. The comparison of clinical, immunological and virological parameters in 91 children with HIV infection with rapid (26%) and slow progression of the disease (74%) was carried out. The criterion for the rapid progression of HIV infection was considered the development of the AIDS clinic in the first two years of life.Results. Testing of clinical, immunological and virological parameters in a multivariate logistic regression model revealed independent predictors of rapid progression in children aged 6 months - HIV blood viral load more than 1 00 000 cop./ml (odds ratio OR 23.9; 95% confidence interval 95% CI 4.6-71.8; P < 0.001) and a decrease of blood CD4-lymphocytes less than 25% (OR 6.3; 95% CI 1.2-33.4; P = 0.029). The predictor «HIV blood viral load more than 100 000 cop./ml» was characterized by a higher sensitivity (91.3%), specificity (97.1 %) compared to the indicator «CD4 lymphocyte count less than 25%» (88.2% and 86.9%).Conclusion. In 26% of children with HIV infection, there is a rapid progression of the disease with the development of AIDS clinic during the first two years of life. The independent predictors of forecasting an unfavorable course of the disease are HIV blood viral load of more than 1 00 000 cop./ml and a decrease in CD4 lymphocytes in the blood of less than 25% at the age of 6 months. The level of viremia seems to be more preferable for predicting the course of HIV infection in children due to its high sensitivity and specificity.